Four-component polarization propagator calculations of electron excitations: spectroscopic implications of spin-orbit coupling effects - Pernpointner, Markus; Visscher, Lucas; Trofimov, Alexander (Journal of chemical theory and computation, 2018)
A complete implementation of the polarization propagator based on the Dirac-Coulomb Hamiltonian is presented and applied to excitation spectra of various systems. Hereby the effect of spin-orbit coupling on excitation energies and transition moments is investigated in detail. The individual perturbational contributions to the transition moments could now be separately analyzed for the first time and show the relevance of one- and two-particle terms. In some systems different contributions to the transition moments partially cancel each other and do not allow for simple predictions. For the outer valence spectrum of the H2Os(CO)4 complex a detailed final state analysis is performed explaining the sensitivity of the excitation spectrum to spin-orbit effects. Finally, technical issues of handling double group symmetry in the relativistic framework and methodological aspects of our parallel implementation are discussed.
Gesehen am 23.08.2019